2017
DOI: 10.1016/j.firesaf.2017.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Real-time evacuation route selection methodology for complex buildings

Abstract: This paper proposes a new real-time decision method to select optimal evacuation routes. The mathematical formulation, the solution algorithm and the computer model are presented. The optimization algorithm is based on the stochastic evacuation model predictions by considering emergency data such as the location of the hazard. The method was applied to an industrial building. The stochastic evacuation model was compared with the commercial evacuation model STEPS involving 14 potential evacuation routes and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…According to Cuesta et al [22], exit time is influenced by: The layout and distance to be travelled by people; bottleneck points; added times relative to different circumstances and choices; and speed of movement of the people. We consider "exit time" to be the interval between the moment the sirens start to sound until the moment when no more people come out of the building, the moment that consider to be the end of the evacuation.…”
Section: Our Proposalmentioning
confidence: 99%
“…According to Cuesta et al [22], exit time is influenced by: The layout and distance to be travelled by people; bottleneck points; added times relative to different circumstances and choices; and speed of movement of the people. We consider "exit time" to be the interval between the moment the sirens start to sound until the moment when no more people come out of the building, the moment that consider to be the end of the evacuation.…”
Section: Our Proposalmentioning
confidence: 99%
“…The study did not provide enough information about the computational load, the time required for modeling, and how they addressed the challenges of using positioning techniques in indoor spaces. In another research, predictions of stochastic evacuation models were used to generate the optimal evacuation routes in real-time [2]. The framework lacked explicit attention to hazard detection and threat propagation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lin and Wang (2017) demonstrated that the spread of the accidental building fire and further forecast smoke dispersion can be estimated in real time. Cuesta et al (2017) proposed a real-time decision for the selection of optimal evacuation routes for buildings, based on static plans and signaling, but the changing conditions during the emergency were not considered in their model. Considering the route coordination problem, Lujak et al (2017) introduced real-time evacuation guidance.…”
Section: Iot-based Real Time Intelligent Routingmentioning
confidence: 99%